Ekonomicheskie aspekty sistemy meditsinskogo obespecheniya sportsmenov i lits, zanimayushchikhcya fizicheskoi kul'turoi i sportom - Kostenko, S. A. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The aim of this paper was to consider the problem of the economic aspect in medical providing of athletes and persons acting in the system of sport for all. The authors discuss the methods of the economical efficiency`s evaluation for various components of medical providing in physical culture and sport. They analyze the sports medicine`s influence on the national economy in positive as well as in negative sense. They consider the economy of medical-prophylactic providing in physical culture and sport as the interdisciplinary scientific area.